Mujahid bin Jabr (d. 104 AH), an Interpretive Figure | مجاهد بن جبر – رحمه الله (ت 104 هـ) شخصية تفسيرية - Ahmad Kusjairi Suhail (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2017)
The one who undertakes the interpretation of the Noble Qur’an and tries to understand its words, verses, rulings, and what it contains of commands and intentions, and carries out the task of enlightening people with the Book of God, which is the orbit of the religion of Islam and calling them to it, is the most honorable of people and has a high status among all scholars, just as his work is one of the noblest purposes and the most rewarding deeds. Numerous texts have been received from the Holy Qur’an, the Sunnah of the Prophet, and the works of the righteous predecessors, which indicate the high status of the interpreter among all scholars.